POST – CRISIS EXCHANGE RATE POLICY IN INDONESIA - Ilman, Abdul Hadi (Jurnal TAMBORA, 2017)
In 1997 Indonesia was hit by a severe financial crisis which led to the change of almost everything in the country, including the exchange rate regime; from managed floating to free floating or flexible exchange rate. It has been a major conclusion from academic debate that maintaining exchange rate at a certain level or band (soft peg) was no longer workable in the more integrated financial system, international market, and free flow of capital mobility across economy.Indonesia once was known as one of the “Asian Tigers” which were believed to be the next industrialized economies as was being indicated by astounding macroeconomic performance since the early 1990s. The exchange rate management, in which the objective was to have a competitiveness in the international market, was making a huge contribution to that performance. No one suspected those countries would be hit by the crisis until Thailand’s Bath was under attacked and suddenly it spread expeditiously to other economies.Domestically, economy of Indonesia was funded by foreign debt in the several years before crisis to leverage the economy, especially private sector. Thus, when the currency crisis was happening, the value of rupiah was depreciated so much and the central bank could not afford to stabilize the value of rupiah in the market. Then a huge amount of the dollar-denominated short term debt was suspected to default since the debt value in rupiah was becoming very large.